21st century educational technology adoption in accounting education: Does institutional support moderates accounting educators acceptance behaviour and conscientiousness trait towards behavioural intention? - Mat Dangi, Mohamad Ridhuan (Human Resource Management Academic Research Society, 2021)
This study examines the interaction effects of institutional support between the educators’ conscientiousness traits and acceptance behaviour towards their behavioural intention to adopt educational technology. Simple random sampling and questionnaire survey methods were used on university educators from several public universities in Malaysia, offering bachelor's degree programmes in accounting. Data were analysed using structural equation modelling to achieve the study’s objectives. This study found that perceived usefulness, attitudes, and conscientiousness are significant, suggesting their important role as predictors of educational technology adoption among accounting educators. Meanwhile, institutional support is able to moderate the acceptance behaviour of accounting educators in the matter of usefulness, ease of use, and attitudes towards the behavioural intention to use educational technology; however, it has no interaction effect on conscientiousness. This study provides valuable insights into understanding the factors influencing accounting educators’ intention to integrate technology in the teaching and learning activities of the 21st century environment.